Proteomic differences between developmental stages of Toxoplasma gondii revealed by iTRAQ-based quantitative proteomics - Wang, Ze-Xiang; Zhou, Chun-Xue; Elsheikha, Hany M.; He, Shuai; Zhou, Dong-Hui; Zhu, Xing-Quan (Frontiers, 2017)
Toxoplasma gondii has a complex two-host life-cycle between intermediate host and definitive host. Understanding proteomic variations across the life-cycle stages of T. gondii may improve the understanding of molecular adaption mechanism of T. gondii across life-cycle stages, and should have implications for the development of new treatment and prevention interventions against T. gondii infection. Here, we utilized LC–MS/MS coupled with iTRAQ labeling technology to identify differentially expressed proteins (DEPs) specific to tachyzoite (T), bradyzoites-containing cyst (C) and sporulated oocyst (O) stages of the cyst-forming T. gondii Prugniuad (Pru) strain. A total of 6285 proteins were identified in the three developmental stages of T. gondii. Our analysis also revealed 875, 656, and 538 DEPs in O vs. T, T vs. C, and C vs. O, respectively. The up- and down-regulated proteins were analyzed by Gene Ontology enrichment, KEGG pathway and STRING analyses. Some virulence-related factors and ribosomal proteins exhibited distinct expression patterns across the life-cycle stages. The virulence factors expressed in sporulated oocysts and the number of up-regulated virulence factors in the cyst stage were about twice as many as in tachyzoites. Of the 79 ribosomal proteins identified in T. gondii, the number of up-regulated ribosomal proteins was 33 and 46 in sporulated oocysts and cysts, respectively, compared with tachyzoites. These results support the hypothesis that oocyst and cystic stages are able to adapt to adverse environmental conditions and selection pressures induced by the host’s immune response, respectively. These findings have important implications for understanding of the developmental biology of T. gondii, which may facilitate the discovery of novel therapeutic targets to better control toxoplasmosis.